Local heat transfer coefficient measurements on an engine-representative internal cooling passage - Ryley, JR; McGilvray, M; Gillespie, DRH (American Institute of Aeronautics and Astronautics, 2018)
Spatially resolved heat transfer measurements of turbomachinery components can lead to more accurate metal temperature distributions, leading to better predictions of thermal stresses in the blade and, ultimately, blade life. The increased fidelity of the spatially resolved data also provides a data set, which can delineate the complex fluid and heat transfer processes for the purpose of numerical validation. This research applies transient liquid crystal experiments on stationary engine-representative internal cooling passages with a filleted rectangular cross section and staggered 45 deg ribs on two opposing walls. The ribs have a rounded profile and span half the width of the passage. Pressure loss measurements and spatially resolved heat transfer coefficients have been collected over the full surface of the test section over a range of Reynolds numbers (18,000–105,000) for three aspect ratios (1∶2, 1∶3, and 1∶4). The experimental results were compared to widely used empirical correlations for ribbed passages with full-width ribs in sharp-cornered passages. The average Nusselt number and friction factor differed from industry-standard correlations by a maximum of 45 and 10%, respectively.